Unraveling structural features of flavodiiron proteins: a detailed structural insight for oxygen or nitric oxide reduction - Borges, Patrícia Alexandra Teixeira (2022)
"The work presented in this dissertation focuses on Flavodiiron Proteins (FDPs), a family of enzymes able to reduce oxygen and/or nitric oxide into water or non-toxic nitrous oxide. FDPs are widespread in prokaryotes and unicellular eukaryotes as well as in phototrophs, from cyanobacteria and unicellular algae to higher plants. The FDP minimal structural unit is composed of two domains: a metallo-β-lactamase- like domain at the N-terminal harbouring a diiron catalytic center and a flavodoxin-like domain at the C-terminal containing a non-covalently bound flavin mononucleotide (FMN). The diiron site is where the substrate reduction occurs while the FMN cofactor shuttles the electrons to this catalytic center. The two redox centers within the same monomer are too far away (~40 Å) to allow an efficient electron transfer between them. Therefore, the minimal functional unit of FDPs, consists of a homodimer with a “head-to-tail” arrangement, which brings close together (~6 Å) the diiron center of one monomer and the FMN cofactor of the neighbouring monomer. (...)"